Non Alcoholic Fatty Liver Disease - Ali Hussein mahdi abd; Areej Qasim majeed hasan; Zahraa Hussein Raheef Malhoud; Ayat Rashad Ismail Malik (American Journal of Biomedicine and Pharmacy, 2025)
Health care providers divide fatty liver disease into two types. If the fat accumulate but no damage to liver occur, the disease is called nonalcoholic fatty liver disease (NAFLD). If fat accumulate in liver plus signs of inflammation and liver cell damage, the disease is called nonalcoholic steatohepatitis (NASH). Non-alcoholic fatty liver disease (NAFLD) is a common disorder and refers to a group of defects where there is accumulation of excess fat in the liver of people who drink little or no alcohol. The most common form of NAFLD is a non-serious condition called fatty liver. In fatty liver, fat accumulates in the liver cells. Although having fat in the liver is not normal, by itself it probably does not damage the liver. A small group of people with NAFLD may have a more serious condition named non-alcoholic steatohepatitis (NASH). In NASH, fat accumulation is associated with liver cell inflammation and different degrees of scarring. NASH is a potentially serious condition that may lead to severe liver scarring and cirrhosis. Cirrhosis occurs when the liver sustains substantial damage, and the liver cells are gradually replaced by scar tissue which results in the inability of the liver to work properly. Some patients who develop cirrhosis may eventually require a liver transplant.